(3GdCQHYjf GdjefjI aj GdCMGOjK GdfHhjIs - (3GdbGVj CMeO Hf YHO Gddg Hf Ydj GdhGOYj GdaVjdj, Uaj GdOjfs
(3ChdgG (B:s
(3GdMeO ddg eSNQ GdGadGc CeG HYO aEfi deG hQO ef cd eJbOe hLOJ Ydi eYfi bhdg Ydjg GdSdGe (B( (3ef MaX Ydi GeJi GQHYjf MOjKkG (B) (3GdMOjK s
(3BNQgG (B:s
( (3hGdPjf ge Yf CjGJfG ZGadhf ChdFc eGhGge GdfGQ HeG cGfhG jcSHhf (B) (3GdGjI Je MOjK GdGQHYjf s
(3QhGjI Yf TjhNgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs